(untitled) (Research, Society and Development, 2022)
The patellar dislocation corresponds to the displacement of the patella of the trochlear groove. In the small animal clinic is one of the most common orthopedic problems, especially in dogs, however the cats are rarely affected. The objective of this study was to report a case of medial patellar dislocation grade IV in feline, through the description of the surgical technique, as well as to evaluate the benefits of the therapy for the welfare of the animal. A feline, by the Brazilian short arrived at the clinic presenting lameness and the patella was moved medially to the physical examination. The X-ray revealed hip dysplasia, bilateral patellar dislocation and rotation in the distal portion of the femur. Surgical therapy was chosen by deepening the trochlear groove with a cylindrical file up to 50% of the patellar thickness and lateral imbrication of the patella with anchorage of the fabela with attachment to the tibial tuberosity at "8" and imbrication sutures in the fibrous joint capsule and on the lateral border of the patellar tendon. The surgical correction provided quality of life to the patient and allowed the animal to resume the activities characteristic of its species.